(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mahatma Basaveshwara was the founder of Lingayat /Virasaiva religion in Karnataka in India. He was a social- economic, religious, and political, culture and literature reformer of 12th century. He was the founder of Anubhava Mantapa (First World Parliament) in Kalyana (now called as Basavakalya). And wrote Vachanas (prose-poetry literature) in Kannada. His period also called as the Vachana Yuga. Along with him other 770 Vachanakaras (those who wrote Vachanas) and 33 women Vachanakartis wrote Vachanas and enriched the Kannada literature and culture. Most of the Vachanakaras Vachanas focuses on welfare of all human beings. While studying Vachanas we also found the those focuses on against caste system, emancipation of women, upliftment of Dalits and untouchability, mystical and spiritual knowledge, Istalinga worship, Virasaiva tenets and practices by devotees. Even these Vachana Sahitya is unique in Indian Literature and Culture. It has its own form, characteristics, and methods. While studying the Vachanas one has to balance the spiritual and material life. While I am studying Vachanakaras Vachanas I found that many Vachanakaras focuses on the morality, non-violence, truth, inner and outer purity, mind concentration and welfare of all humanbeings. In this paper selected Vachanakaras (Shivasharanas ) focuses on mental health and wellbeing Vachanas considered for study. The eminent Vachanakaras like Basaveshwara, Allamaprabhu, Akkamahadevi , Siddharameshwara and Chennabasaveshwaras, Jedara Dasimaya, Urlilinga , Molige Marayya, Nuliya Candayya,Revamma, Akkama, Madivala Machideva, Sakalesha Maadarasa, Sarvadya Vachana’s reviewed for this research work. These Shivasharanas Vachanas help us to purify our mental, spiritual, social, economic, and cultural self.